Animasi The Amazing World of Gumball: Representasi Keberagaman Visual dalam Artstyle - Arbi, Hafiz; Sari, Intan Permata; Juhana, Agus (Universitas Komputer Indonesia, 2024)
Animation is an effective narrative medium that captures theaudience's attention through a combination of technology, visual aesthetics, and storytelling. The evolution from traditional animation to computer generated imagery has opened up opportunities for visual innovation. The animated series The Amazing World of Gumball stands out for its use of various animation techniques, including traditional 2D animation, CGI, stop-motion, and live-action. This study aims to analyze the visual diversity in the series and the importance of varied art styles in shaping visual narratives. The diverse animation techniques strengthen the visual identity and narrative, making the series more engaging and recognizable. The use of bright colors and different techniques helps create dynamic moods and emotions, appealing to audiences of all ages. This study emphasizes that visual diversity not only enriches aesthetics but also deepens the narrative, inviting viewers to engage more deeply and understand the conveyed messages. For future research, it is recommended to explore the specific impact of each animation technique on audience engagement in other animated series.